Storytelling an encyclopedia of mythology and folklore - Sherman, Josepha; Gale Group (Armonk, N.Y. M.E. Sharpe, 2008)
A collection of informative entries providing a definitive study of the wide world of storytelling.
v. 1. Aarne, Antti (1867?1925)-Gudrun/Kudrun (German) -- v. 2. Habaek and Haemosu (Korean)-Symphonic/Tone Poems -- v. 3. Tail Tales-Zwarte Madam (Flemish).
Electronic reproduction.
Keywords: Folklore -- Encyclopedias; Mythology -- Encyclopedias; Storytelling -- Encyclopedias; Electronic books